The Child in Irish Poetry: From Yeats to the Present - Orchard, Ellen Clare (Trinity College Dublin. School of English. Discipline of English, 2025)
This project is the first full length study of the child in Irish poetry. It spotlights the hurt and endangered child in the work of eight poets, who write in or about twentieth-century Ireland: Eavan Boland, Kimberly Campanello, Austin Clarke, Leontia Flynn, Seamus Heaney, Paula Meehan and Eiléan Ní Chuilleanáin. Working at the critical intersection of the ideological contexts of childhood and real, (auto)biographical childhood experience, this thesis is interested in how poetry attempts to communicate actual childhood experience. This thesis advocates for the gendered dimension of writing childhoods, arguing for the relative lack of girlhoods in Irish poetry and builds on literary criticism which reads the child in Irish poetry as a vehicle for cultural nationalism, particularly in a young Republic. Its spirit of inquiry is driven by the tension between the Proclamation's promise of `cherishing all the children of the nation equally', and the various gruelling circumstances in which children found themselves in twentieth-century Ireland, such as widespread abuse suffered in schools as well as institutionalisation in orphanages, Mother and Baby Homes and Magdalene Laundries. In taking a long view of the twentieth century, across the whole island, this thesis concludes that rather than acting as a symbol for the nation, the child in modern Irish poetry more often embodies the nation's failings.
APPROVED
Keywords: Nationalism; The Troubles; Girlhood; Irish Poetry; Childhood